Towards Rare-Functionalized N-Alkenyl-1H-pyrroles via Regioselectively Metalated N-Isopropenyl-1H-pyrroles - Tarasova, Ol'ga A.; Maximova, Marina A.; Albanov, Alexander I.; Nedolya, Nina A.; Trofimov, Boris A. (Synthesis, 2022)
Deprotonative metalation of N-isopropenyl-1H-pyrroles with superbases followed by trapping with a variety of electrophiles was studied as an effective tool for the regioselective functionalization of 1H-pyrroles.
Keywords: N-isopropenyl-1H-pyrrole; N-isopropenyl-4,5,6,7-tetrahydro-1H-indole; superbases; metalation; functionalization